Riesgo moral e información oculta antes de la conformación de equipos; Moral hazard and hidden information before the formation of the teams - Andrés Cendales; Jhon James Mora (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2020)
– In the context of the team's theory, this article shows that employees will be communicated, independent of their skill endowment, have a high skill endowment. In this way, the formation teams can lead to groups whose productivity is lower than that exhibited in terms of the skills they communicated before the formation of the team. The formation of teams with agents and skills does not correspond to the information they have communicated in their messages, it leads to coordination problems that affect the performance of the team due the heterogeneity of the principal's in the team. An example of this is the formation of academic teams in universities.
Keywords: C72; C70; D31; 330; moral hazard in teams; incentive compatibility; hidden information